GSK-3 and BCL-XL inhibition mitigates the competitive advantage of APC-mutant colorectal cancer cells - Le Zhang; Lidia Atencia Taboada; Selami Baglamis; Maartje de Kroon; Carolien Elshout; Prashanthi Ramesh; Roxan F.C.P.A Helderman; Arezo Torang; Kate Cameron; Milou S. van Driel; Valérie M. Wouters; Sanne M. van Neerven; et al. (Oncogenesis)
Abstract BCL-XL is a crucial anti-apoptotic protein that supports survival of intestinal cells during the progression and in established colorectal cancer (CRC). While targeting BCL-XL with BH3 mimetics is effective, its significant toxicity highlights the need for alternative approaches. Importantly, the early steps in intestinal transformation are marked by a competition between normal and transformed stem cells in which the mutant cells gain a supercompetitive advantage due to the secretion of WNT inhibitors. Using multiple human and murine CRC models, we revealed that GSK-3 inhibition strongly sensitized to BH3 mimetic-induced killing. As expected, GSK-3 inhibition significantly upregulated the WNT pathway, but also led to marked enhancement of BH3 mimetic-induced apoptosis, as measured by mitochondrial BAX aggregation, Caspase-3 activation and Propidium Iodide exclusion. Furthermore, GSK-3 inhibition provided an advantage to wild-type intestinal organoids in competition with APC-mutant counterparts due to reactivation of the WNT pathway. More strikingly, combining GSK-3 and BCL-XL inhibition profoundly affected the supercompetition APC-mutant intestinal cells exert over the wild-types. In effect, the combination therapy enhanced the competitive fitness of wild-type cells and resulted in the killing of APC-mutant organoids, pointing to a novel combination therapy that can be further exploited in the treatment of adenomas and CRC.